O consumo da habitação de luxo no espaço urbano parisiense - Andréa Rodrigues dos Santos (Confins)
The objective of this work is to understand the luxury concept in the context of Parisian housing and identify the geographic location of this segment in its urban space. With more than two million inhabitants, Paris city concentrates different fractions of social classes, which are distributed by the twenty districts that comprise it. However, is in its central portion and southwest direction which are the most luxurious neighborhoods in the city with a concentration of buildings that gather a set of objective factors (such as the prime location, large balconies, presence of garages, access control, personnel service among others) and subjectives (the fact of provide comfort, status, social distinction and lifestyles) that provide the parameters that help to understand the meaning of luxury housing in this city. The understanding of this concept was provided in the readings from authors who worked the issue, through fieldwork and interviews in real estate marketing group responsible for these properties in Paris